Anthropology and Sociology of Law as Interdisciplinary Formation - Peña Jumpa, Antonio (2010)
This paper is about the anthropology and sociology of law as an interdisciplinary education. The author starts pointing what we do understand by interdisciplinary: two or more integrated disciplines that co-work to achieve the same goal. He points that this work is enlightening for the involved disciplines. Furthermore, he indicates the differences of this concept with the multidisciplinary and the transdisciplinary. Further on, he mentions that the interdisciplinary education has the learning and teaching as a key aspects in order to accomplish a deeper understanding. He specifies that we found the interdisciplinary education in three levels: research work, educational work and professional career; however, he elaborates the first two only. Then, he points the experience of the interdisciplinary education as a legal anthropology and as a legal sociology. First, from the legal anthropology we have the following. On the one hand, on the research work the law and anthropology contributions, each one of this own point of view, allows understand the phenomenon and project solutions. On the other hand, in the educational work, the teaching from these two disciplines projects that the student has a broader perspective of the phenomenon. Second, form the legal sociology, in the research work, are addressed the causes and the legal effects of some phenomenon. In this part, the Sociology contributes the study of facts and finds to transform the qualitative data into quantitative, as well as he gives an objective approximation over the phenomenon, while the Law gives a value contribution. Likewise, from the educational work, this education helps to teach lawyers to have a broader perspective than the study of the law, as well the sociologist do not keep in the study of facts, but he knows about the preexistence of the institutional order. Finally, the author raises the goals that emerged due to this view of education and he emphasizes that the dialogue is essential between the involved disciplines in order to achieve solutions to address the study of some phenomenon. In addition, he considers that it must promote, innovate, multiply and reinforce the interdisciplinary educations and the investigation activities.